Mind the Links! How Hyperlinks Influence Online Reading and Navigation : An Eye Movement Study - Martikainen, Hanna (fi=Turun yliopisto|en=University of Turku|, 2017)
In this thesis, the eye movement methodology is used to explore the influence of hyperlinks and reading task on online reading in a navigable Web environment. The amount of research on hypertext reading is limited, and the understanding of hypertext processing is only developing. The previous eye movement studies conducted in a non-navigable web environment suggest that the hyperlinked words are not more difficult to process than unlinked words. The research also suggests that in the skim reading task, hyperlinked words are less likely to be skipped, and when they are fixated, they are processed more carefully than unlinked words. In this experiment, the possibility to click and navigate the hypertext made it possible to explore how the hyperlinks are processed in a more authentic Web environment. It was expected that the results from this experiment would be similar than those observed in previous studies: hyperlinked words would not be more difficult to process than unlinked words, and in the skim reading task, hyperlinked words would be processed more carefully than unlinked words. In the study design, thirty-two native English speakers read and navigated hypertext in a Wikipedia environment while their eye movements were recorded. The results indicate that hyperlinked words are not more difficult to process than unlinked words, but readers do focus on hyperlinked words. The results were not clear on whether the hyperlinked words were processed differently across the reading for comprehension and skim reading tasks. The early processing of hyperlinks was more careful compared to the unlinked words in the skimming task. Hyperlinks received more fixations, and their later processing was more careful than that of the unlinked words in both tasks. The results add to evidence that the visible form of hyperlink is not problematic for reading processes, but what words are selected as hyperlinks should be considered in user optimal web design. It is necessary to further explore reading and navigation on the web, with realistic tasks and in different web environments. It is also important to investigate how hypertexts are used in wider learning processes. Exploring how cognitive resources and individual differences influence hypertext processing is also crucial to find out how hypertexts can be made accessible and beneficial for all the users.